„Noise made from interaction between tires and pavement surface and measures for protection from it at long distance roads“ - Mijoski G., Zileska-Pancovska V. (Faculty of Mining, Geology and Civil Engineering, University of Tuzla in co-operation with Geotechnical Society in Bosnia and Herzegovina, 2012)
The noise has great influence on the environment and represents a serious problem, because it contributes for significant reduction of the life quality of the people. In order of the influences on the environment the noise it’s on the very top, together with the pollution of the air and the water. It’s very important to point out that the noise has bad influence not only on the environment, but also on the driver and the passengers in the car. Special accent in the paper is put on the noise caused from the motor traffic- socalled traffic noise, which is dependant from the surface characteristics of the pavement surfaces.
Keywords: noise, pavement surface, tires, measures for noise protection, acoustic barrier